AERODYNAMIC PERFORMANCE ANALYSIS OF S809 AIRFOIL APPLICATION ON HORIZONTAL AXIS WIND TURBINE BLADES - Hadi, Alpan (Journal of Innovation Research and Knowledge, 2025)
This study analyzes the aerodynamic effects of using the S809 airfoil on the blades of a horizontal-axis wind turbine (HAWT) type AWT-27. The S809 airfoil is designed for low-speed applications, making it aerodynamically suitable for optimizing wind turbine performance in regions with moderate to low wind speeds. Simulations were conducted using Blade Element Momentum Theory (BEMT) based software to evaluate power and power coefficient at various wind speeds. The results indicate that AWT-27 blades with the S809 airfoil deliver better aerodynamic performance at low wind speeds, ranging from 5 m/s to 8 m/s. However, the aerodynamic performance decreases at higher wind speeds, between 9 m/s and 25 m/s. Therefore, AWT-27 blades with the S809 airfoil profile can be an effective alternative for enhancing the performance of horizontal-axis wind turbines, particularly in regions with low wind speeds.